Pesticide Risk Valuation in Empirical Economics - Peter Nijkamp; Chiara Maria Travisi; Gabriella Vindigni (Tinbergen Institute, 2002)
Pesticide use in agriculture poses several risks to both human health and non-target agro-ecosystems. Due to lack of information on the monetary value of reducing pesticide risks, it is difficult to perform an economic analysis that addresses social efficiency of policy and draws conclusions about the appropriate degree of regulation.The aim of the current paper is to present a critical overview of the empirical literature on pesticide risk valuation that provides disaggregate willingness-to-pay estimates (WTPs) of pesticide risks reduction. Recent multidimensional classification methods, such as coined decision tree analysis, are used in a comparative approach as tools for explaining the differences in empirical research findings. The analysis shows that the magnitude of WTPs is related to both the valuation technique and to the data available from biomedical and eco-toxicological literature. It also shows that WTP estimates of pesticide risks cannot be simply averaged over several empirical studies. The order of magnitude of a WTP estimate is, in fact, related to the specific type of risk and to the nature of the risk scenario considered, as well to lay people's subjective perception of risks.
Keywords: Q10; 330; pesticide environmental and health risks; willingness-to-pay; comparative analysis.; Pestizid; Landwirtschaft; Umweltbelastung; Willingness to pay; Theorie